Report of the High Powered Study Group on Establishment of New Stock Exchanges - Planning Commission (Planning Commission, 1991)
Indian Stock Exchanges have witnessed phenomenal growth during the 1980s. The number of Stock Exchanges, the number of listed Companies, market capitalisation and trading volumes have all grown substantially. However, this growth has not been even across Stock Exchanges, and inter-se variations exist. There is adequate evidence that bears testimony of a substantial increase in the investor base, both in absolute numbers, as well as in terms of geographical distribution. There is also wide spread recognition that the servicing of investors is poor, and small investors in the smaller Exchanges are not able to participate effectively in the secondary market
Report of the High Powered Study Group on Establishment of New Stock Exchanges
Planning Commission